The Play as Intellectual Ping-Pong: Art and Politics in Tom Stoppard's Travesties (Journal of the College of Languages (JCL), 2006)
Throughout history, artists have played many important roles in society.Generally speaking, the role of the artist is defined by the society he is part of.Indeed, there are as many ideas as to the role of the artist and, ultimately the purposeof art in society, as there are types of art. This is, as a matter of fact, neither a newquestion- the dialogue has been present within art for centuries- nor probably onethat will ever fully be answered.Tom Stoppard came to prominence in the mid-sixties, when art and politicswere closely linked, and theatre sought to change the world. Stoppard would havenone of that: his work has no overt message, no political program. In fact, whatStoppard has resisted both in his plays and in his interviews is any idea of the theatreas an agent of change, as a form of art which is in any sense expressive andcontributory to the nature of the society of which it is a part. (Philip Roberts, p.85)This is especially true of Stoppard's early dramatic works which, he told the Gambitin 1981, "could best be seen in terms of his sense of alienation from the Osbornianschool of angry young men writing socially-engaged drama."(Neil Sammelles,p.131)This aspect in Stoppard's early dramatic career did not go unnoticed by thecritics who severely criticize him for his alleged indifference to contemporarysocial issues; a tendency which turned his early plays, according to Roberts, intoapolitical opportunities for "wit, parody and metaphysical dalliance."(p.87)